PENGELOLAAN PERILAKU SISWA OLEH GURU DI SEKOLAH TUNAS HARAPAN NUSANTARA BEKASI JAWA BARAT - Tumanggor, Raja Oloan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2018)
Teachers have an important role in improving education of students in schools. However, teachers often deal with the fact that students behave in a way that is not supportive towards effective teaching and learning process such as disturbing peers during studying, making noise in the classroom, being disorderly and lacking discipline in learning. For this reason, teachers need to be equipped with the knowledge and skills to manage the behavior of uncooperative students. As many as 24 elementary and middle school teachers from Tunas Harapan Nusantara Bekasi school were provided with strategies to manage student behavior in schools to create effective learning conditions.Through lecture, group work and independent work, the teachers are able to explore the potential of the students, so that students’ uncooperative behavior can be directed to positive things. The result is that teachers become skilled at dealing with and managing student behavior in class, teachers have effective strategies to direct students to become diligent learners. The output is the competence of teachers in applying models of student behavior management in schools.ABSTRAK: Guru memiliki peranan penting dalam meningkatkan pendidikan peserta didik di sekolah. Namun guru kerap berhadapan dengan kenyataan bahwa para siswa memiliki perilaku yang tidak mendukung terciptanya proses belajar mengajar secara efektif seperti misalnya suka mengganggu teman siswa sewaktu belajar, membuat keributan di kelas, tidak tertib dan kurang disiplin dalam belajar. Untuk itu guru perlu dibekali pengetahuan dan keterampilan mengelola perilaku siswa-siswa yang tidak mendukung tersebut. Sebanyak 24 orang guru SD dan SMP di sekolah Tunas Harapan Nusantara Bekasi didampingi bagaimana strategi mengelola perilaku siswa di sekolah agar tercipta kondisi belajar yang efektif. Dengan metode ceramah, kerja kelompok dan kerja mandiri para guru dimampukan menggali potensi yang dimiliki oleh siswa sehingga perilaku siswa yang kurang mendukung pembelajaran bisa diarahkan ke hal-hal positif. Hasil akhirnya adalah para guru menjadi terampil menghadapi dan mengelola perilaku siswa di kelas dan memiliki strategi efektif untuk mengarahkan siswa menjadi pembelajar yang tekun. Luarannya adalah kompetensi para guru dalam menerapkan model-model pengelolaan perilaku siswa di sekolah.